2015
DOI: 10.1111/cpf.12261
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate mouth rinse enhances time to exhaustion during treadmill exercise

Abstract: Mouth rinsing with a CHO solution has been suggested to improve short (<1 h) endurance performance through central effect. We examined the effects of mouth rinsing with a CHO solution on running time to exhaustion on a treadmill. Six well-trained subjects ran to exhaustion at 85% VO , on three separate occasions. Subjects received either an 8% CHO solution or a placebo (PLA) every 15 min to mouth rinse (MR) or a 6% CHO solution to ingest (ING). Treatments were assigned in a randomized, counterbalanced fashion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 31 publications
(57 reference statements)
4
34
1
4
Order By: Relevance
“…Similarly, pacing strategy did not differ between conditions (i.e., CHO mouth rinse and PLA) throughout the trial. Despite several studies [ 1 , 3 , 24 ] showing that CHO mouth rinse is effective to improve cycling performance, our results corroborate those of others showing no benefits in using this strategy [ 7 , 9 , 25 , 26 ]. Some aspects could be highlighted to discuss this controversy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, pacing strategy did not differ between conditions (i.e., CHO mouth rinse and PLA) throughout the trial. Despite several studies [ 1 , 3 , 24 ] showing that CHO mouth rinse is effective to improve cycling performance, our results corroborate those of others showing no benefits in using this strategy [ 7 , 9 , 25 , 26 ]. Some aspects could be highlighted to discuss this controversy.…”
Section: Discussionsupporting
confidence: 85%
“…Although some studies have shown benefits of CHO mouth rinse on performance in both fed and fasted states [ 2 , 31 ], some showed improvements only if participants commenced the exercise in a fasted state (>4 h fasting) [ 3 , 24 ] and others failed to show improvements with CHO mouth rinse in a fed state [ 25 , 26 ], thereby leading to inconclusive interpretations about the influence of the pre-exercise fasting period. There is a questionable applicability of this intervention in real-world situations, as athletes (recreational or professional) usually avoid to train and compete in a fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…This result is very interesting since results are mixed and most studies have failed to observe benefits from CHO MR [9,44,75,76,77] and CAF MR [18,78] on perception of effort. Only a few studies have reported that CAF and CHO MR could lead to a decrease in RPE [25,26,27] suggesting that CHO and CAF MR induce a decrease in subjective perception of effort, allowing participants to produce more power with the same degree of discomfort.…”
Section: Discussionmentioning
confidence: 89%
“…Open-ended test where subjects are required to exercise at a constant work rate for as long as possible have been criticized due to the greater variation in performance time versus closed-end tests where subjects are required to cover a given distance in the quickest time possible or ride for a given time period and told to complete the greatest distance possible [47]. However, it should be noted that not all studies using open-ended tests have reported large variations in exercise time [48], and studies have reported differences in exercise time when evaluating the effects of other nutritional supplements [49].…”
mentioning
confidence: 99%